Fetal arthrogryposis: Challenges and perspectives for prenatal detection and management. Issue 3 (18th July 2019) - Filges, Isabel; Tercanli, Sevgi; Hall, Judith G.
Abstract: Antenatal identification of fetuses with multiple congenital contractures or arthrogryposis multiplex congenita (AMC) may be challenging. The first clinical sign is often reduced fetal movement and/or contractures, as seen on prenatal ultrasounds. This can be apparent at any point, from early to late pregnancy, may range from mild to severe involvement, with or without associated other structural anomalies. Possible etiologies and their prognosis need to be interpreted with respect to developmental timing. The etiology of AMC is highly heterogeneous and making the specific diagnosis will guide prognosis, counseling and prenatal and perinatal management. Current ultrasound practice identifies only approximately 25% of individuals with arthrogryposis prenatally before 24 weeks of pregnancy in a general obstetrics care population. There are currently no studies and guidelines that address the question of when and how to assess for fetal contractures and movements during pregnancy. The failure to identify fetuses with arthrogryposis before 24 weeks of pregnancy means that physicians and families are denied reproductive options and interventions that may improve outcome. We review current practice and recommend adjusting the current prenatal imaging and genetic diagnostic strategies to achieve early prenatal detection and etiologic diagnosis. We suggest exploring options for in utero therapy to increase fetal movement for ongoing pregnancies.